A rare case of plexiform schwannoma of the lower lip: Treatment and management - Subha Dhua (Indian Journal of Plastic Surgery)
An 18-year-old female presented with a swelling on the lower lip, which was insidious in onset and gradually progressive. The mass was completely excised under local anaesthesia. Complete histopathologic and immunohistochemical studies were conducted. The Antoni A areas were found along with typical verocay bodies composed of palisading nuclei and surrounding spaces filled with eosinophilic filaments. No necrosis was noted and there were no atypical mitotic figures. In the Antoni B region, a closely textured matrix with areas of edema, myxomatous changes, cystic degeneration and dilated vessels were noted. On the basis of the histopathologic and immunohistochemical staining with S-100 protein, a diagnosis of plexiform schwannoma was made and has been reported in this study. The post-operative view confirmed complete recovery after 6 weeks of surgery. This is a rare case with the tumour located in the lower lip, as very few cases have been reported in literature and it may be the first one reported from India.